2016
DOI: 10.1371/journal.pntd.0004826
|View full text |Cite
|
Sign up to set email alerts
|

Recent Duplication and Functional Divergence in Parasitic Nematode Levamisole-Sensitive Acetylcholine Receptors

Abstract: Helminth parasites rely on fast-synaptic transmission in their neuromusculature to experience the outside world and respond to it. Acetylcholine plays a pivotal role in this and its receptors are targeted by a wide variety of both natural and synthetic compounds used in human health and for the control of parasitic disease. The model, Caenorhabditis elegans is characterized by a large number of acetylcholine receptor subunit genes, a feature shared across the nematodes. This dynamic family is characterized by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 62 publications
0
42
0
Order By: Relevance
“…Recently, we showed that C . elegans was a tractable model to express AChR receptors from parasitic nematode species [ 35 , 38 , 39 ]. Therefore, to address the functional relationship between ACR-8 and LEV-8, we conducted an in vivo characterization of the parasitic nematode ACR-8 using C .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we showed that C . elegans was a tractable model to express AChR receptors from parasitic nematode species [ 35 , 38 , 39 ]. Therefore, to address the functional relationship between ACR-8 and LEV-8, we conducted an in vivo characterization of the parasitic nematode ACR-8 using C .…”
Section: Resultsmentioning
confidence: 99%
“…contortus : Hco-L-AChR-1.3 and Hco-L-AChR-1.4. [ 35 ]. Both receptors that differed in their subunit composition by the presence of distinct H .…”
Section: Introductionmentioning
confidence: 99%
“…An analysis of genomic data from 25 nematode parasite species indicated multiple independent duplications of unc-29 as positive, directional selections acting on amino acid positions associated with subunit assembly. It has been demonstrated that functional divergence in AChRs with novel pharmacology occurs more rapidly and may be mediated by alteration of receptor assembly, providing a foundation for understanding the broader context of changing anthelmintic drug targets across the parasitic nematodes [ 61 ]. Furthermore, identification of four gene copies of AChRs from the sheep nematode, Haemonchus contortus , also demonstrated that each copy has acquired unique functional characteristics [ 61 ].…”
Section: Ache and Achrs In Other Helminthsmentioning
confidence: 99%
“…Parasitic nematodes contain nAChR subunit genes that show high similarity with their C. elegans counterparts. Whereas C. elegans muscle contains two main nAChR subtypes (L-and N-) of fixed subunit composition, parasitic nematode muscle has a greater diversity of nAChRs owing to subunit duplication and to different arrangements of the orthologous subunits (Qian et al, 2006;Boulin et al, 2008Boulin et al, , 2011Buxton et al, 2014;Duguet et al, 2016;Verma et al, 2017). In different species, L-, N-, P-(pyrantel), M-(morantel), and B-(bephenium) subtypes have been described (Martin et al, 1997;Robertson et al, 2002;Qian et al, 2006;Verma et al, 2017).…”
Section: Introductionmentioning
confidence: 99%